2016
DOI: 10.31234/osf.io/8p67h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of salience in young children's processing of ad-hoc implicatures

Abstract: Language comprehension often requires making implicatures. For example, inferring that "I ate some of the cookies" implicates the speaker ate some but not all (scalar implicatures); and "I ate the chocolate-chip cookies" where there are both chocolate chip cookies and raisin cookies in the context implicates that the speaker ate the chocolate chip, but not both the chocolate chip and raisin cookies (ad-hoc implicatures). Children’s ability to make scalar implicatures develops around age five, with ad-hoc impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
2
11
1
Order By: Relevance
“…Reaction time differences that were previously only evidenced in adults (Hamblin & Gibbs, 2003), were found for children in our study. In line with previous developmental studies on other pragmatic tasks (such as scalar implicature comprehension or reference resolution, see: Graham et al, 2014;Huang & Snedeker, 2009;Khu et al, 2019;Nadig & Sedivy, 2002;Nilsen et al, 2008;Yoon et al, 2015), we also found elaborate fixation patterns for those utterances that required more inferencing, that is, for indirect communicative acts. Moreover, we replicated developmental effects concerning children's object-choice performance that is in line with the children's general development of pragmatic phenomena (e.g., ad hoc quantity inferences, scalar inferences, see Wilson & Katsos, 2020;Wilson, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Reaction time differences that were previously only evidenced in adults (Hamblin & Gibbs, 2003), were found for children in our study. In line with previous developmental studies on other pragmatic tasks (such as scalar implicature comprehension or reference resolution, see: Graham et al, 2014;Huang & Snedeker, 2009;Khu et al, 2019;Nadig & Sedivy, 2002;Nilsen et al, 2008;Yoon et al, 2015), we also found elaborate fixation patterns for those utterances that required more inferencing, that is, for indirect communicative acts. Moreover, we replicated developmental effects concerning children's object-choice performance that is in line with the children's general development of pragmatic phenomena (e.g., ad hoc quantity inferences, scalar inferences, see Wilson & Katsos, 2020;Wilson, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, given that studies on children's looking behavior in other pragmatic tasks (such as scalar implicature comprehension or reference resolution) found elaborate fixation patterns for utterances that required inferencing (Graham et al, 2014;Huang & Snedeker, 2009;Khu et al, 2019;Nadig & Sedivy, 2002;Nilsen et al, 2008;Yoon et al, 2015), we expected to find more elaborate fixation patterns for indirect compared to direct communicative acts.…”
mentioning
confidence: 96%
“…By age two, children are sensitive to the informativeness of communication (O'Neill & Topolovec, 2001). By age three children can use this expectation to make pragmatic inferences (Stiller, Goodman, & Frank, 2015;Yoon & Frank, 2019) and to infer novel word meanings (Frank & Goodman, 2014). And although older children continue to struggle with some complex pragmatic inferences until age five and beyond (Noveck, 2001), an emerging consensus identifies these difficulties as stemming from difficulties reasoning about linguistic alternatives rather than pragmatic deficits (Barner, Brooks, & Bale, 2011;Horowitz, Schneider, & Frank, 2018;Skordos & Papafragou, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many past studies have found that, while children readily apply exclusion inferences like contrast and mutual exclusivity during word learning, they take many years to exhibit adult-like behavior when computing scalar implicatures (e.g., that an utterance containing some implies 'not all'). However, a number of recent studies have reported surprisingly early successes at scalar implicature, usually using forced choice paradigms or direct contrast of scalar alternatives (Miller et al, 2005;Papafragou & Tantalou, 2004;Skordos & Papafragou, 2016;Stiller et al, 2015;Yoon et al, 2015). Based on these findings, we explored the possibility that some children's earliest successes on purported tests of scalar implicature could instead be explained by appeal to exclusion inference (e.g., inference driven by contrast or mutual exclusivity).…”
Section: Discussionmentioning
confidence: 95%
“…Finally, although exclusion inferences may involve asymmetric entailment (e.g., cat vs. animal), this is not a requirement, unlike in the case of scalar implicature. Papafragou & Musolino, 2003), and others finding evidence of scalar implicature in school-aged children (Chierchia, Crain, Guasti, Gualmini, & Meroni, 2001;Guasti et al, 2005;Katsos & Bishop, 2011) and in preschoolers as young as three years of age (Miller, Schmitt, Chang, & Munn, 2005;Papafragou & Tantalou, 2004;Stiller, Goodman, & Frank, 2015;Syrett & Arunachalam, 2016;Yoon, Wu, & Frank, 2015).…”
mentioning
confidence: 97%